Internacionalização organizacional e cultura: as relações públicas no processo interno de mudança - Val, Kely de Morais [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The ever more interconnected and competitive markets have contributed to the increase in the number of companies seeking mergers and acquisitions, as they undergo significant cultural dimensions that can influence the success of an organization. This study analyses how the process of change can happen, considering the importance of culture, the complexities of the internal public and the interaction between professionals, with the aid of Public Relations. The analysis is grounded on theoretical principles concerning intercultural communication and the role of the professional as a manager of communicational barriers. It also recommends the application of storytelling as an organizational strategy in order to mediate potentially conflicting changes that could be facilitated with the work of Public Relations

Mercados cada vez mais interligados e competitivos têm assistido ao crescimento do número de empresas que buscam por fusões e aquisições, atravessando dimensões culturais significativas que podem influenciar o sucesso organizacional. Este estudo analisa como o processo de mudança pode ocorrer, considerando a importância da cultura, das especificidades do público interno e da interação entre profissionais, com a contribuição das Relações Públicas. A reflexão é sustentada por bases teóricas sobre a comunicação intercultural e o papel do profissional como gestor das barreiras comunicacionais. Propõe-se ainda a implementação da estratégia de storytelling a fim de mediar mudanças potencialmente conflituosas que podem ser facilitadas por meio da atuação das Relações Públicas
Keywords: Pluralismo cultural; Comunicação intercultural; Desenvolvimento organizacional; Relações publicas; Cultural pluralism